Correlation between praecordial accelerocardiogram and left ventricular pressure. Issue 3 (March 1976) - Hume, L; Kitchin, A H; Reuben, S R
Abstract : The praecordial accelerocardiogram possesses important practical advantages over more familiar techniques of recording praecordial pulsations. We have compared the amplitude of the P wave of the praecordial accelerocardiogram in 6 normal subjects (group 1) and 21 patients with heart disease (group 2) at rest and after 3 minutes of isometric handgrip at 30 per cent maximum voluntary contraction. At rest in group 2 there was a significant linear correlation between the amplitude of the P wave of the accelerocardiogram, relative to the maximum systolic amplitude (P/DE), and the left ventricular end-diastolic pressure (P less than 0-01). However, comparison of the data for P/DE showed that the mean value (+/-SEM) of 29+/-5 per cent in group 1 was not significantly different from the mean value of 37+/-4 per cent in group 2 (P g .reater than 0-30). During handgrip the mean amplitude of the P wave did not increase significantly in group 1 (P greater than 0-20) but increased significantly in group 2 (P less than 0-02). In group 2 there was a significant linear correlation between the percentage increase in the amplitude of the P wave of the accelerocardiogram during handgrip and the percentage increase in the left ventricular end-diastolic pressure (P less than 0-01).